2004
DOI: 10.1109/twc.2004.837407
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Carrier Phase Recovery Suited to Turbo-Coded Systems

Abstract: Abstract-This paper examines the problem of carrier phase recovery in turbo-coded systems. We introduce a new concept of "a priori probability aided phase estimation", where the extrinsic information (log-likelihood ratio) obtained from turbo decoder is used to aid an iterative phase estimation process, which is based on a maximum-likelihood strategy. The phase estimator operates jointly with the turbo decoding rather than separately prior to the decoder as in traditional approaches. This technique provides re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…Express the received signal as r i ¼ A i expðjf i Þ, where A i denotes the amplitude and f i represents the argument; both vary due to the existence of the carrier phase error and the noise. The expression of LLF for the ith received symbol can be written as [3] …”
Section: Joint Turbo Decoding and Phase Estimationmentioning
confidence: 99%
“…Express the received signal as r i ¼ A i expðjf i Þ, where A i denotes the amplitude and f i represents the argument; both vary due to the existence of the carrier phase error and the noise. The expression of LLF for the ith received symbol can be written as [3] …”
Section: Joint Turbo Decoding and Phase Estimationmentioning
confidence: 99%
“…To this end, several studies have attempted to overcome channel effects by means of carrier phase error correction [17][18][19][20]. Steendam et al [17] investigated the effects of carrier phase offsets on a low-density parity-check (LDPC) coded system, and then proposed a maximum likelihood (ML)-based carrier phase synchronization algorithm that exploits the posterior probabilities of the data symbols.…”
Section: Introductionmentioning
confidence: 99%
“…Steendam et al [17] investigated the effects of carrier phase offsets on a low-density parity-check (LDPC) coded system, and then proposed a maximum likelihood (ML)-based carrier phase synchronization algorithm that exploits the posterior probabilities of the data symbols. Similarly, Zhang et al [18] proposed an a priori probability aided carrier phase estimation for turbo decoding. They showed that the physical (PHY) layer technique provides a reliable carrier phase estimation that approaches the Cramer-Rao bounds at a very low signal-to-noise ratio (SNR).…”
Section: Introductionmentioning
confidence: 99%
“…None of these papers take into account the parity bits in the turbo iteration process. [4] considered that the extrinsic information obtained from turbo decoder is only for the information bits, so the paper only used the information bits in the carrier estimator. V. Lottici introduced a low-complexity carrier phase estimation algorithm that integrated into the data decoder of a turbo-coded system [5].…”
Section: Introductionmentioning
confidence: 99%